Fight or flight [videorecording (Blu-Ray)] - McLaren, Brooks; Cotrona, D. J. (Donald Joseph), 1980-; Hartnett, Josh, 1978-; Chandran, Charithra; Zaror, Marko, 1978-; Chan, JuJu, 1987-; Kostov, Julian; Baxter, Declan; O'Donnell, Hughie; Ashok, Danny; Sackhoff, Katee; Flannery, Matt, 1981-; et al. (Vertical Entertainment, 2025)
A mercenary takes on the job of tracking a high-value asset known only as "The Ghost" on an international flight. Realizing the plane is filled with assassins assigned to kill them both, the pair must work together in a fight for their lives.